The Sultan's Life as a Tragedy? Zeyā al-Din Barani, Moʿezz al-Din Keyqobād, and the Performance of Tārikh. Issue 1 (January 2022) - Trausch, Tilmann
Abstract : This article examines how Zeyā al-Din Barani may have imagined that contemporary audiences would consume his Tārikh-e Firuz Shāhi. Would it only be read visually or also read aloud (directed at the ear rather than the eye), and thus be received aurally, or would it even be performed in front of a larger audience? The plot and protagonists of Barani's story on Moʿezz al-Din Keyqobād present a tragedy that develops around a sultan doomed to fail. An examination of the set-up of Barani's narrative reveals that it contains numerous textual devices that would enable a storyteller to perform the story, using the text as a kind of tumār. As tragedies are written for the stage, not the study, these features of the text indicate that matters of orality, which are crucial for many genres of premodern Persianate courtly literature, are also relevant to the Tārikh-e Firuz Shāhi.